2012
DOI: 10.1074/jbc.m111.316489
|View full text |Cite
|
Sign up to set email alerts
|

The Replication-independent Histone H3-H4 Chaperones HIR, ASF1, and RTT106 Co-operate to Maintain Promoter Fidelity

Abstract: Background: Transcription is disruptive to chromatin structure and can expose cryptic promoters. Results: We identify those factors that might regulate cryptic transcription from within inactive and transcribed locations. Conclusion: Nucleosome shielding prevents cryptic transcription, and replication-independent histone replacement is co-operatively mediated by three H3-H4 chaperones. Significance: Understanding how cryptic transcription is regulated and lost histones replaced is of fundamental importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
62
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 63 publications
7
62
2
Order By: Relevance
“…Notably, the deletion of RTT109 or ASF1, which prevents H3K56 acetylation and consequently decreases Rtt106:H3 binding, reduces Rtt106 enrichment at histone promoters ( Fig. 1A and B) (32,33,51) without reducing HIR localization (Fig. 1C) (16).…”
Section: Rtt106:h3 Binding Was Required For Histone Gene Repressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, the deletion of RTT109 or ASF1, which prevents H3K56 acetylation and consequently decreases Rtt106:H3 binding, reduces Rtt106 enrichment at histone promoters ( Fig. 1A and B) (32,33,51) without reducing HIR localization (Fig. 1C) (16).…”
Section: Rtt106:h3 Binding Was Required For Histone Gene Repressionmentioning
confidence: 99%
“…Mutations that disrupt Rtt106:H3 binding lead to reduced Rtt106 enrichment at histone gene promoters (32,51), suggesting that the Rtt106:HIR interaction might be mediated by histone proteins. Asf1 copurifies with the HIR complex (21), and in asf1⌬ cells, Rtt106 localization is reduced, leading to inappropriate histone expression outside S phase (51,53). Although these data suggest that Asf1 plays a direct role in histone gene regulation, whether Asf1 localizes to histone gene promoters as a member of the HIR:Rtt106 regulatory complex was unclear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the complementary experiment we observed that the HIR2 deletion did not affect rrm3D viability ( Figure S1). Given that HIR2 is required for the integrity of the HIR complex and, consequently, for histone deposition activity of Asf1/HIR (Green et al 2005;Silva et al 2012), these observations demonstrate that the replicationindependent chromatin assembly function of Asf1 is not required for rrm3D cell viability. We next evaluated the contribution of the single-residue substitution V94R, important for histone H3 interaction (Mousson et al 2005;Jiao et al 2012).…”
mentioning
confidence: 80%